2013
DOI: 10.9787/pbb.2013.1.1.009
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of dlm and ti genes in Soybean

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT dlm mutant newly identified displays necrotic spots with chlorotic halo despite the absence of any detectable pathogens in soybean. Kunitz trypsin inhibitor (KTI) protein of mature soybean seed is a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
2
1
0
Order By: Relevance
“…The segregation ratio for the presence or absence of lectin protein in the F2 seed generation was well fitted to an expected 3:1 ratio (χ 2 =2.28, P=0.5-0.01). These results substantiate earlier reports that Le locus is inherited as a single gene (Orf and Hymowitz 1979b;Sung et al 2013).…”
Section: Discussionsupporting
confidence: 82%
“…The segregation ratio for the presence or absence of lectin protein in the F2 seed generation was well fitted to an expected 3:1 ratio (χ 2 =2.28, P=0.5-0.01). These results substantiate earlier reports that Le locus is inherited as a single gene (Orf and Hymowitz 1979b;Sung et al 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Also, a 3:1 segregation ratio was observed (χ 2 = 2.59, P=0.5 -0.1) for the presence or absence of lectin protein in the F 2 seed generation. This result substantiate previous observations that lectin protein is controlled by a single gene (Choi et al 2016;Sung et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, the dlm phenotype was found to be light-dependent and associated with chloroplast function [15]. Inheritance of dlm mutant phenotype and some leaf morphological traits were carried out, and it was reported the dlm allele inherited independently with that of P1 , y9 , f , lf2 and ti alleles controlling glabrous, chlorophyll-deficient leaf, stem trait, seven leaflet and trypsin inhibitors traits in soybean, respectively [17,18]. Wang et al [19] found a new LMM in soybean with rugose leaf phenotype controlled by two duplicated genes, rf1 , and rf2 , which were mapped on chromosome 18 and 08, respectively.…”
Section: Introductionmentioning
confidence: 99%